STUDY OF THE COMPOSITION OF MICROFLORA OF ROOT CANALS IN PRIMARY AND CHRONIC PERIODONTITIS - S.O. Priadko; I.P. Koshova; A.V. Samoilenko (Український стоматологічний альманах)
The problem of chronic focal infection of the pulp and periodontal tissues is relevant for both therapeutic and surgical dentistry. It has been proven that the long-term effect of microbial flora on the filling material, root dentin, periodontium and bone tissue often leads to destructive lesions of the periodontal tissues.